Ratifikasi Konvensi Jenewa 1949 Dalam Hukum Humaniter Internasional - Adelle Constanza Pariela; Johanis Steny Franco Peilouw; Ekberth Vallen Noya (Faculty of Law Universitas Pattimura, 2026)
The Geneva Conventions 1949 are an international humanitarian law document that regulates the protection of war victims and forms the basis for states participating in international humanitarian law. On October 10, 2023, Israel attacked the area of ​​Al-Karama, a Palestinian people's group; this action violated the Geneva Convention 1949 for the Protection of Victims of War, one of the sources of IHL law. Through a review of the literature, primary, secondary, and tertiary data will be gathered and analyzed in this normative-juridical study. To shed light on the topics raised, the legal discipline analyzes this evidence qualitatively and compiles it in a methodical manner. The purpose of this essay is to evaluate the Geneva Convention 1949 as an instrument of international humanitarian law. The results of this study indicate that ratifying the Geneva Convention 1949 along with Additional Protocols I and II is not a state obligation. Although basically this is an obligation that cannot be ignored within the scope of HHI because it is one of the main sources of HHI law. The Geneva Conventions 1949 apply to all situations of war that are contained in the provisions of this convention. If there is a violation of the contents of the convention, the perpetrators of the crime can be held accountable as agents of the state, reparations and receive international sanctions and pressure.